A prayer for Owen Meany : a novel - Irving, John, 1942- (New York : Ballantine Books, 1990)
Tells the story of Owen Meany who believes he is God's instrument and his friendship with John Wheelwright; beginning at age eleven when Owen hits a foul ball that kills John's mother during a Little League game in 1953.
Booklist.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Young Adult
Keywords: Friendship -- Fiction; Christian fiction; Friendship -- Fiction; New Hampshire -- Fiction; New Hampshire -- Fiction